Compare the Effects of Dexmedetomidine and Metoprolol in Reducing Blood Loss During Craniotomy - Faheem Asghar, Umar Iqbal, Mamoona Shaikh (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of current study is to compare the effects of dexmedetomidine and metoprolol in reducing blood loss during craniotomy. Study Design: Randomized Double bind Place and Duration: Conducted at M.Islam Medical College Gujranwala/Rashid Latif Medical College Lahore, during from Feb 2021 to September 2021. Methods: There were seventy patients of both genders were included in this study. Craniotomy patients with severe head injuries were presented.Age, gender, and BMI were all collected after informed written agreement was obtained from all participants.Patients were divided into two groups. Group I had 35 patients and received metroprolol while group II had 35 patients and received dexmedetomidine during craniotomy. Outcomes among both were assessed and compared in terms of blood loss, heart rate and blood pressure during the surgery. The full dataset was analyzed using SPSS 24.0. Results:There were 20 (57.1%) males and 15 (42.9%) females in group I while in group II 22 (62.9%) males and 13 (37.1%) females. In group I mean age was 49.4±4.13 years with mean BMI 24.9±5.23 kg/m2 and in group II mean age was 50.7±5.42 years with mean BMI 24.8±6.32 kg/m2. Mean blood loss after 2 hours of surgery in group II was lower 411.4±6.34 ml as compared to group I 512.7±8.55 ml. Mean heart rate 71.4±6.17 beats/min and blood pressure 70.3±4.23 mmHg in group I was higher as compared to group II 68.9±7.31 beats/min and 66.10±8.34 mmHg. Conclusion:We concluded in this study that the dexmedetomidine was effective in terms to reduce blood loss and maintain blood pressure and heart beat of cases as compared to metroprolol during craniotomy among patients.